Correlation of cheek biting with stress and salivary cortisol in final-year dentistry students: a cross-sectional study - Mentari, Diana Gita; Sabirin, Indah Puti Rahmayani; Safira, Rheni; Sulaksana, Sutrania Dewi (Padjadjaran Journal of Dentistry, 2024)
Introduction: Stress is a situation that can feel self-threatening, arising from stressors that exceed the body's ability to cope. Final-year students are particularly vulnerable to stress as they face the pressure of completing their theses. Cheek biting is recognized as a coping mechanism for psychological stress, which is why it is often associated with stress. The purpose of this study is to analyze the correlation between stress levels and the occurrence of cheek biting in final-year students. Methods: This research was an observational study with a cross-sectional approach. The research subjects were final-year students who were completing their theses. The sample size was determined using the correlation sample size formula and employed total sampling, including 40 respondents based on the inclusion criteria. A perceived stress score (PSS-10) questionnaire, salivary cortisol examination, and cheek biting assessment were conducted for all respondents. Results: PSS-10 examination results revealed that five students had a low stress level, 29 students had a moderate stress level, and six students had high levels of psychological stress. The Spearman correlation coefficient between stress perception and cheek biting incidents was 0.638, which indicated a strong relationship and was statistically significant (p-value=0.001). However, salivary cortisol examination of ten respondents with cheek biting showed only slightly higher levels than the control group, and the Mann-Whitney test showed no significant differences. Conclusion: There was a moderate correlation between perceived stress levels and the occurrence of cheek biting in the final-year dentistry students in the Faculty of Dentistry, Jendral Ahmad Yani University, Indonesia. However, there was no difference in salivary cortisol level when compared to students without cheek biting.